Inselbergs shaped by collapse: considerations on the structural control on granitic scarps - Maia , Rubson Pinheiro; Souza, Anna Sabrina Vidal de (Revista Brasileira de Geomorfologia, 2024)
Inselbergs characterised by fracturing features correspond to the geomorphological manifestation of break-up of the rock mass and collapse. The steep slopes partially covered by angular boulders scattered chaotically reveal, in evolutionary terms, the predominance of the morphostructural controls, given by the presence of veins/dikes, sheeting joints, and vertical fractures. These structural planes in turn create anisotropies guiding fracturing directions and rockfall. In this work, we propose a model of geomorphological evolution of granitic inselbergs subjected to a structural propensity to fracturing. For this purpose, we analysed the Pedra da Galinha Choca inselberg (PGC) and Pedra Faladeira (Quixadá, NE of Brazil) inselbergs, whose morphologies attest to mechanical disintegration processes. Data extraction and interpretation were based on fieldwork and UAV photogrammetry, which provided products such as high-resolution models, orthomosaic, and DEM. Networks of multidirectional fractures were observed to promote an arrangement of interlocking blocks, allowing the maintenance of steep slopes (>60°), in which solutional features tend to be incipient due to the structural instability promoting collapse. Thus, the main features on the hillslopes are cavities like collapse tafone (CT) and large collapsed boulders (LCB). As a result of this structural setting, the inselberg displays sharp outlines, steep slopes, and wide talu deposits.